Proactive Planning for Breastfeeding Assistance and Support Post Birth. Issue 6 (November 2021) - Spatz, Diane L.
Abstract : During prenatal care, nurses can help families develop a breastfeeding plan for promoting milk supply after birth. A hospital grade breast pump is essential if the baby is not effectively latching or if there a maternal or infant risk factor that could affect coming to volume. Families should be aware there is a critical window for milk supply to effectively be established. Our breastfeeding expert, Dr. Spatz, covers what should be included in a breastfeeding plan.